Cyclic behavior of polypropylene fiber reinforced concrete beams with prestressed CFRP tendons and nonprestressed steel bars. (15th January 2023) - Peng, Fei; Xue, Weichen; Yu, Tianqi
Highlights: Cyclic behavior of FRC beams with prestressed CFRP tendons and nonprestressed steel bars was investigated. Effects of partial prestressing ratio, reinforcing index, and prestressing level on ductility and deformability were evaluated. Compression failure was a more favorable failure mode compared to the tension failure. Design recommendations were made to ensure a minimum curvature ductility of 2.0. Abstract: The main purpose of this paper is to evaluate the cyclic behavior of polypropylene fiber-reinforced concrete (FRC) beams with a hybrid reinforcement system of prestressed carbon fiber reinforced polymer (CFRP) tendons and nonprestressed steel bars. A total of six beams are tested, including four beams prestressed with CFRP tendons, one prestressed with steel tendons and one reinforced with steel bars. The experimental variables include the partial prestressing ratio, amount of CFRP tendons, and jacking stress level. The test results are presented in terms of failure mode, hysteretic response, flexural capacity, self-centering capability, ductility, stiffness degradation and energy dissipation. The results show that the CFRP prestressed beam failing due to concrete crushing exhibits much higher ductility and dissipated energy than the beam failing due to CFRP rupture. An increase in the partial prestressing ratio or a decrease in the jacking stress has a favorable effect on the ductility. A numerical moment–curvature analysis procedure is applied to perform a parametric analysis of the ductility and deformability of the hybrid FRC section. It is recommended that the reinforcing index should be sufficient to ensure compression failure, but should not be greater than 0.35 to ensure reasonable ductility and deformability.